Older patients with vertebral and pelvic fractures: study protocol of a clinical cohort - Roigk, Patrick; Leonhardt, Rebekka; Lindemann, Ulrich; Abel, Bastian; Büchele, Gisela; Rothenbacher, Dietrich; Koschate, Jessica; Schlotmann, Julia; Elsayed, Mohamed; Zieschang, Tania; Laurentius, Thea; Bollheimer, Cornelius; et al. (PLOS ONE, 2024)
Background Vertebral and pelvic fractures are associated with a significant burden of negative health and psychosocial outcomes. The number of vertebral and pelvic fractures is increasing in an aging society. Vertebral and pelvic fractures are increasingly significant injuries for individuals and society. However, few epidemiological studies have examined the clinical course of vertebral and pelvic fractures. This is the protocol for a study that observes patients who have been admitted to the hospital with an incident vertebral or pelvic fracture for a period of 12 months. Methods The observational cohort study is conducted at three study sites in Germany. Patients affected by vertebral or pelvic fractures are recruited within the first few days of hospital admission. Data collection takes place at four-time points: baseline, before discharge, after 4 months, and after 12 months after admission to the hospital. Particular emphasis is laid on the assessment of the fall mechanisms, physical function, physical activity, life space, mobility, treatment approach, and quality of life. The hospital stay involves the collection of biomaterials (blood and urine). Discussion The study aims to enhance understanding of the clinical progression and outcomes in patients with fractures in the vertebrae or pelvis.
Gesehen am 27.03.2025